Mindfull Breathing Training untuk Mereduksi Kecemasan pada Remaja Putri di Panti Asuhan Aisyah Muhammadiyah Banjarmasin - Sabit Tohari; Muhammad Eka Prasetia; Zakiyah Zakiyah (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
Adolescent girls living in orphanages face more complex psychosocial challenges compared to their peers in general. Experiences of loss, limited family support, and uncertainty about the future often lead to heightened anxiety. One effective psychological intervention to manage anxiety is mindful breathing training, or conscious breathing exercises. This community service activity aimed to provide mindful breathing training for adolescent girls at the Aisyiyah Muhammadiyah Orphanage in Banjarmasin as an effort to reduce anxiety and enhance inner calmness. The implementation method employed educational, participatory, and practical approaches, consisting of four stages: preparation, implementation, evaluation, and follow-up. The results of the activity showed that participants gained a good understanding of the concepts of anxiety and mindfulness, and were able to correctly practice the mindful breathing technique. Based on the evaluation results, more than 80% of participants stated that the training was engaging, clear, and beneficial in helping them manage anxiety. Therefore, mindful breathing training proved to be an effective, simple, and applicable strategy for reducing anxiety levels among adolescents in the orphanage.